Cutting-tool delivery method in the context of industrial product service systems. (June 2016) - Sun, Peilu; Zhang, Chaoyang; Jiang, Pingyu; Cao, Wei
Nowadays, as the manufacturing outsourcing activities are becoming increasingly explosive, cutting-tools are gradually being considered as a kind of strategical socialized manufacturing resource. Therefore, focusing on cutting-tools, this article proposes a novel cutting-tool service mode called industrial product service system for cutting-tools. Based on industrial product service system for cutting-tools, the methodology of cutting-tool delivery in the context of industrial product service system is further studied, which comprises two sub-models. First, a cutting-tool demand prediction model is established to obtain the types and quantities of cutting-tool demands in the next day from each industrial product service system for cutting-tool customer. Then, the second sub-model is a just-in-time cutting-tool delivery model, wherein, a modified economic order quantity model and genetic algorithm are applied to optimize the delivery time and routing constrained by the delivery time window. Finally, a comprehensive use case is studied to illustrate the feasibility and applicability of the proposed models.